SATU KATA UNTUK PISPA (SEBAGAI UPAYA PENINGKATAN PENGETAHUAN UNTUK PENCEGAHAN INFEKSI SALURAN PERNAPASAN AKUT) - Nurun Nikmah; Vivin Wijiastutik (STIKES NGUDIA HUSADA MADURA, 2023)
ISPA is an Acute Respiratory Infection which is a disease that contributes to a high prevalence of morbidity in toddlers. The purpose of this community service activity is One Word for PISPA (As an effort to Increase Knowledge about Prevention of Acute Respiratory Infections in Toddlers). In this community service, the counseling method used was first a case study on two randomly selected samples, and then continued with the lecture and question and answer method. The media used were audio-visual equipment, and leaflet printed media were distributed to mothers, which contained information about ARI, namely the definition or meaning of ARI, causes of ARI, signs and symptoms of ARI, factors that cause ARI, efforts to prevent ARI. The result of this activity is an increase in mother's knowledge, namely from good knowledge of 10.00% to 60.00%. Keywords: ARI, Toddlers, Infection, Respiratory Tract, Acute Respiratory Tract